2014
DOI: 10.3109/08923973.2014.909849
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of tea saponin in immune T-cells and T-lymphoma cellsviaregulation of Th1, Th2 immune response and MAPK/ERK2 signaling pathway

Abstract: The anti-cancer activity of saponins and phenolic compounds present in green tea was previously reported. However, the immunomodulatory and adjuvanticity activity of tea saponin has never been studied. In this study, we investigated the immunomodulatory effect of tea saponin in T-lymphocytes and EL4 cells via regulation of cytokine response and mitogen-activated protein kinases (MAPK) signaling pathway. Quantitative analysis of mRNA expression level of cytokines were performed by reverse transcription polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The saponins have been found to have numerous pharmacological effects including anti-fungal [ 29 ], anti-viral [ 30 ], anti-inflammatory [ 31 ], anti-hyperlipidemic [ 32 ], immunomodulatory [ 33 ] and anti-tumor activities [ 17 , 19 ]. Among these, TSE 1 was proved to have higher bioactivity than other saponin monomers present in tea seeds [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The saponins have been found to have numerous pharmacological effects including anti-fungal [ 29 ], anti-viral [ 30 ], anti-inflammatory [ 31 ], anti-hyperlipidemic [ 32 ], immunomodulatory [ 33 ] and anti-tumor activities [ 17 , 19 ]. Among these, TSE 1 was proved to have higher bioactivity than other saponin monomers present in tea seeds [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…TS was isolated from Green tea ( Camellia sinensis (L.) O. Kuntze) seeds, which were freshly harvested from the National germplasm Hangzhou tea tree nursery, Hangzhou, China, and modified by previously-established methods [ 36 ]. Briefly, the dried tea seeds were pulverized and subsequently extracted with 70% MeOH (1:15 w / v ) under reflux for 5 h at 70 °C.…”
Section: Methodsmentioning
confidence: 99%
“…TS has been demonstrated as being an excellent bio-surfactant with numerous pharmacological activities. TS has been documented as having gastroprotective [ 33 ], anti-fungal [ 34 ], anti-viral [ 25 ], anti-oxidative [ 24 ], anti-obesity [ 35 ], anti-inflammatory [ 24 , 28 ], anti-hyperglycemic [ 27 ], immunomodulatory [ 36 ], and anti-tumor [ 35 , 37 , 38 ] tendencies. However, unlike other phenolic compounds, EGCG [ 39 , 40 , 41 ] and TFs [ 37 , 42 ] separated from tea plants, TS has not been reported as having pharmacological influences on human ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has also shown that TSP can improve the permeability of capillaries in hypertensive rats (Sagesaka-Mitane et al, 1996). The lower SCC found after supplementation of 20 and 30 g/d of TSP confirmed its function in immunomodulatory effects (Bhardwaj et al, 2014). Previous studies also found that milk SCC is related to the antioxidant status of the body (Suriyasathaporn et al, 2006).…”
Section: Bloodmentioning
confidence: 78%